Advances in Grape and Wine Biotechnology 2019
DOI: 10.5772/intechopen.87025
|View full text |Cite
|
Sign up to set email alerts
|

Production and Marketing of Low-Alcohol Wine

Abstract: Moderate wine consumption may be associated with specific health benefits and a healthy lifestyle. However, increased amounts of ethanol are cytotoxic and associated with adverse health outcomes. Alcohol reduction in wine might be an avenue to reduce alcohol related harm without forcing consumers to compromise on lifestyle and benefit from positive aspects of moderate consumption. The aim of this review is to give an overview of viticultural and pre and post fermentation methods to produce low-alcohol wine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
(76 reference statements)
0
16
0
Order By: Relevance
“…e enzyme has no significant effect on the aroma, flavour, acidity, and colour of the grape and hence the resultant wine [8,37]. On the contrary, other studies have reported on an increase in total acidity and a slight decrease in pH due to GOX activity, which can affect the sensory properties (taste and flavour) of the wine [38,39].…”
Section: Use Of Glucose Oxidase (Gox)mentioning
confidence: 99%
See 2 more Smart Citations
“…e enzyme has no significant effect on the aroma, flavour, acidity, and colour of the grape and hence the resultant wine [8,37]. On the contrary, other studies have reported on an increase in total acidity and a slight decrease in pH due to GOX activity, which can affect the sensory properties (taste and flavour) of the wine [38,39].…”
Section: Use Of Glucose Oxidase (Gox)mentioning
confidence: 99%
“…Increased oxidation of phenolic substances is a likely explanation for these observations. Commercial preparations of the enzyme added to grape juice were found to reduce ethanol concentration in the resulting wine by 0.68% v/v compared with that of untreated wines [8]. Sensory analysis showed that wines produced from GOX treated must had a lower intensity of fruit aromas, reduced length of flavour, and higher acidity than those of untreated wines [39].…”
Section: Use Of Glucose Oxidase (Gox)mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, H. sabdariffa calyx extract has a characteristic red to red‐brown color which suggests that Roselle calyces extracts may be suitable raw materials for the production of colored wines (Alobo & Offonry, 2009). In recent years, socioeconomic and health‐related factors have resulted in high demand of wines from tropical fruit and vegetables sources with lower alcoholic content (Bucher et al., 2019; Pickering, 2000). Furthermore, the studies conducted by Okoro (2007) on local wine produced from Roselle and pawpaw extracts recorded 10.5% v/v alcohol level, whereas low alcohol content wine should be in the range of 1.2%–5.5% (Erten & Campbell, 2001); hence strong interest to produce wines from tropical fruit and vegetable sources are inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…The latter usually form expectations, before or even during the drinking experience, and influence the perceived quality (Cardello et al , 2007; Grunert et al , 2004). The consumer acceptance and behaviour as related to the low/no alcohol wine case is also reported to be affected by both sensory and information cues (Bucher et al , 2019; Masson et al , 2008).…”
Section: Introductionmentioning
confidence: 99%